Romania: Ready for online learning? - Corina Georgeta Dinculescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The Covid-19 pandemic has had a strong impact on education in Romania and worldwide. Radical measures have been necessary in the field of education, to limit the spread of the virus (like in all the fields affected by the pandemic). One of these measures - the closure of schools, universities and other education institutions and the shift to online learning - has led to a series of disequilibria in the entire education system, with major consequences on pupils/students, mainly in the case of those already vulnerable and disadvantaged. Online learning has been the greatest challenge that the education system has ever faced. The availability of Internet and mobile communication infrastructure, the access of population and education units to Internet and computers, the digital skills of pupils/students as well as of teachers, the availability of school curricula in forms necessary for online presentation have led to this challenge. At the same time, although many young people in Europe use the Internet for social activities, and the mobile Internet access has significantly increased in recent years, the use of technology for education purposes has not followed the same trend. Reducing the negative impact on learning and schooling has therefore been one of the challenges facing the education system.This paper attempts to highlight how the education system has adapted to the restrictions imposed by the pandemic, Romania's readiness, since the pandemic outbreak, for this type of education (through specific indicators on digital skills, connectivity and use of technologies in education, population access to Internet and to a personal computer at home, nationwide and by areas of residence), as well as the gaps between residence areas, between different categories of affected population.
Keywords: I21; I24; J14; J15; R11; 330; education; online learning; disparities in education; urban-rural disparities